Supervision to Improve the Professional Competence of Arabic Language Teachers at the Islamic Boarding School - Syams, Mahmudah; Fathurrahman; Arifin, Ahmad; Darmawaty, Ridha (Jurnal Al-Maqoyis, 2023)
The teacher must possess four competencies, one of wich is professional competence. The teacher’s professionalism has a graet influance on the education process. A professional teacher will create effective education in the classroom. Therefore, the teachers is commmited to improving his efficiency in education in accordance with the development of technology and science. One way to increase it is through intensive supervision with the use of technology in the current era. And the objectives of supervision is to increase the knowledge and experience of the teacher in the implementation of the theacing of the arabic lenguage. And to take advantage of information technology facilities as one of the teacher’s professionalism, especially to improve the teachers in using a strategy and method in the education procces. The scientific journal uses the decriptive qualitatitive type, and the data collection methods are observation, interview, and documentation. In this mentoring there are three stages namely is planning, implementation, and evaluation. The assistance program is carried out for a month with online and offline systems (hybird). And the result of this study indicate the teacher is given YouTube content that is relevant to the goals and learning materials. The teacher designs the lesson and is reviewed by the sacilitator. The teacher applies the learning design in class with the facilitator. Then evaluate and reflect of the implementation of learning. It can be concluded that the use of technology is very large in this supervision program.